PENERAPAN NILAI KODE ETIK KEDOKTERAN INDONESIA PADA ERA JAMINAN KESEHATAN NASIONAL DI KABUPATEN PELALAWAN - Fika, Rana Citra; Afandi, Dedi; Masdar, Huriatul (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTThe Indonesian Code of Medical Ethics or Kode Etik Kedokteran Indonesia (KODEKI) is a guideline for Indonesian doctors that consist of in the form of a set of norms of conduct as reference standards in carrying out everyday medical practice. National Health Insurance (NHI) system has the potential violations of the application of value KODEKI performed by a general practitioners as to make a primary diagnosis according to the coding International Classification of Diseases (ICD-10) that is not in accordance with professional standards. This study aims to determine how the implementation of the KODEKI values in the NHI era in Pelalawan. This study uses exploration method with a qualitative approach. The sample consisted of four doctors who were selected using snowball sampling technique. The data collection was done by in depth interview and recorded with the tape recorder. The result showed that all informants to contain the value of altruism, responsibility, idealism profession, accountability, integrity, scientific, and social integrity. This result shows that the general practitioners in Pelalawan have good implementation of KODEKI values. It can be seen from the statement and the general attitude of the doctors every day.Keywords: KODEKI value, NHI, Pelalawan Regency